Global Sourcing: Towards an Empirical Test of the Hold-up Model - Wilhelm Kohler; Marcel Smolka (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We use Spanish firm-level data to test the hold-up model of global sourcing proposed by Antr s & Helpman (2004). We propose a novel representation of the model which guides us in bringing the theory to the data. We estimate a discrete choice model of firms' sourcing behavior, separately for the location choice and the ownership choice of sourcing. We find that a firm's productivity interacts with an industry's headquarter intensity in governing both dimensions of sourcing in the way suggested by the Antras-Helpman model. In addition, estimated ``ex ante sourcing premia'' of firms lend brought support to the idea that firms self-select into sourcing activities.
Keywords: F12; F23; F14; 330